Urgent Need of Integrated Health and Social Care to Alleviate High Psychological Distress in People with Disabilities: A Cross-Sectional National Representative Survey in Australia - Du W; Wang J; Zhou Q (Dove Medical Press, 2021)
Wei Du,1,2 Jiali Wang,3,4 Qingsheng Zhou5 1School of Public Health, Southeast University, Nanjing, People’s Republic of China; 2Research School of Population Health, Australian National University, Canberra, Australia; 3Research School of Finance, Actuarial Studies & Statistics, Australian National University, Canberra, Australia; 4Massachusetts Eye and Ear Institute, Harvard University, Cambridge, USA; 5Faculty of Health Science, University of Sydney, Sydney, AustraliaCorrespondence: Wei Du Tel +86 25 8327 2303Email duwei@seu.edu.cnObjective: To investigate factors in association with high psychological distress in people with disabilities.Methods: We used the 2015 national survey on disability in Australia to derive the representative study population of 7936 people with disabilities aged 18+ years. The Kessler Psychological Distress Scale (K10) was used to define high psychological distress (scores ≥ 22). The explanatory variables included socioeconomic status, physical health, social relationships and environment factors. Adjusted Odds Ratios (ORs) and 95% Confidence Intervals (CIs) were evaluated using weighted Logistic regression models with lasso techniques.Results: Approximately 21 in 100 study participants experienced high psychological distress. The risk of high psychological distress decreased with age and high educational attainment. Having non-English speaking background (2.31; 1.87– 2.85) and need for assistance in cognitive or emotional tasks (3.25; 2.65– 3.98) were independently significantly associated with high psychological distress in people with disabilities. Delay seeing a GP was associated with a 2-fold risk increase.Conclusion: Integrated healthcare and social support are warranted with appropriate targeting to improve mental health outcomes in people with disabilities.Keywords: people with disability, high psychological distress, integrated healthcare, social support